Assessment of Acrylic-Colored Gross Specimens as Visual Aids in Human Anatomy Laboratories: An Experimental Approach to Museum Preparation - Shrestha, Sunil; Sharma, Nitasha; Bhattrai, Saru; Shah, Ajay (Med Phoenix, 2025)
Introduction: Human anatomy is an integral aspect of the curriculum in the first and second year of the medical educational programs in Nepal. A visually appealing and inventive anatomical color museum can help a medical student’s interest in anatomy education. Therefore, the objective of this research is to establish acrylic colored anatomy museum prototype for instructional purposes for medical students. Materials and methods: 9 anatomically distortion-free specimens from arterial embalmed cadavers were chosen from the department of anatomy of Universal College of Medical Sciences in Bhairahawa, Nepal, which were ethically approved by UCMS/IRC/034/23 for use in research and teaching purpose. Results: The observational photographic result of colored gross specimen was obtained showing colored specimen of Heart, Lungs, Liver and Kidney. The acrylic coloring technique applied to the wet specimen enhances understanding of the physical characteristics and gives the specimen a shimmering appearance that helps to create museum within limited budget. Conclusion: The acrylic colored specimen is simple cost-effective technique which has great importance in teaching learning process of human anatomy.